Source Contribution of Firecrackers Burst vs. Long-Range Transport of Biomass Burning Emissions Over an Urban Background - Rajput, Prashant; Singh, Amit Kumar; Biswas, Kaniska; Qadri, Adnan Mateen; Gupta, Tarun (Frontiers in Sustainable Cities, 2021)
This study reports on the high-resolution data set of ground-level O3, surface-bound polycyclic aromatic hydrocarbons (SB-PAHs), and particle's number concentrations (range: 10 to 1,000 nm, referred to as condensation nucleus concentration: CNC) during a Diwali festival campaign (conducted from 08th to 16th Nov.2015) at Kanpur location. In this study, we have made an attempt to assess the change in atmospheric composition and chemistry (based on SB-PAHs, O3, and CNC) during Diwali festival (11th Nov.) and compared the results with pre-Diwali (08th−10th Nov.) and post-Diwali (12th−16th Nov.) scenarios. The wind pattern and cluster analysis have revealed a quite similar feature that from 10th to 16th of November the prevailed winds were north-westerly (NW). It is noteworthy that NW-winds during post-monsoon season (Oct–Nov) favors the long-range transport of biomass burning emissions (LRT-BB) from its source region in upwind Indo-Gangetic Plain (IGP). The influence of LRT-BB emissions at the receptor site during Diwali and post-Diwali period was reflected by the substantial increase in average concentrations of PM2.5, O3 and CNC (difference has been ascertained from a two-tailed t-test). The Lenshchow-type analysis revealed that the firecrackers (FC) burst and LRT-BB emissions have lead to increase the concentrations of CNC by 54% and 86%, respectively over the urban background level. On the other hand, the FC burst and LRT-BB increased the concentrations of O3 by 12% and 31% (over the urban background), respectively. Lenschow-type analysis revealed that FC burst and LRT-BB increased the daily PM2.5 concentration by 11% and 36%, respectively over its urban background level (286 μg m−3). However, the SB-PAHs concentrations were found to be decreased by 6% and 2%, respectively, during the FC burst activity and LRT-BB emissions. Based on the observations pertaining to the decrease in SB-PAHs concentrations from the Lenschow-type analysis and anti-correlation between SB-PAHs and O3 the heterogeneous-phase chemical reactivity and loss of SB-PAHs has been inferred in this study.